The moral work of anthropology : ethnographic studies of anthropologists at work - Mogensen, Hanne Overgaard; Hansen, Birgitte Gorm (Anthropology at work, 2021)
"Looking at the ways in which anthropologists try to lead positive lives at work, this book investigates what kind of morality they perform in their occupations and what the impact of this morality is. The book includes ethnographic studies in four professional arenas: health care, business, management and interdisciplinary research. The discussion is positioned at the intersection of 'applied or public anthropology' and 'the anthropology of ethics' and analyses the ways in which anthropologists can carry out 'moral work' both inside and outside of academia"--